Causes of Elementary School Children Having Low Affectivity - Delfiyan Widiyanto; Farikah Farikah; Triantono Triantono; Ipung Hananto; Jendriadi Jendriadi; Umi Rachmawati; Linda Eka Pradita; Annisa Istiqomah (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The behavior of elementary school students is caused by students' low affective competence. Problems related to elementary school students that occur in the city of Magelang include various deviations in students' attitudes, namely being difficult to manage in class and at school, bad words, and behavior against teachers. This weak student behavior is due to the students' low affective competence. The presence of this research wants to explore more deeply regarding student deviation and the management of affective competence. Apart from that, researchers will explore in more depth the causes of students' low affective competence. The hope with this research is to improve the quality of education and educate a golden generation with character. This research uses qualitative ethnographic research to explore more deeply the affective competence of students and the causes of low affective competence. This type of research is descriptive with mixed research methods. Quantitative research methods are used to measure students' affective abilities using questionnaire data collection techniques, observation and documentation. Qualitative research methods were used to determine the causes of students' low affective abilities. Data collection techniques include observation, interviews or FGD, and documentation. This research was conducted at SD Negeri Wates 3 in Magelang City. The results of the research show that the overall affective abilities of students are very good, but there are low affective abilities in learning as many as 5 students, and the affective abilities of students in the school environment are 8 students. This low affective ability is caused by wrong parenting patterns from parents, excessive use of technology, and students' friendship environment.